1997
DOI: 10.1084/jem.186.3.405
|View full text |Cite
|
Sign up to set email alerts
|

Two Orphan Seven-Transmembrane Segment Receptors Which Are Expressed in CD4-positive Cells Support Simian Immunodeficiency Virus Infection

Abstract: Clinical isolates of primate immunodeficiency viruses, including human immunodeficiency virus type 1 (HIV-1), enter target cells by sequential binding to CD4 and the chemokine receptor CCR5, a member of the seven-transmembrane receptor family. HIV-1 variants which use additional chemokine receptors are present in the central nervous system or emerge during the course of infection. Simian immunodeficiency viruses (SIV) have been shown to use CCR5 as a coreceptor, but no other receptors for these viruses have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
210
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(220 citation statements)
references
References 70 publications
9
210
1
Order By: Relevance
“…HIV uses CXCR4 as an alternative coreceptor, whereas SIVs use several chemokine orphan receptors such as BOB/GPR15 and Bonzo/STRL33/CXCR6 for efficient infection and replication in vitro. [181][182][183] Several lines of evidence indicated that in vitro BOB/GPR15 is an important SIV coreceptor [184][185][186] exhibiting greater activity than CCR5. 184 Several reports have found that nonpathogenic SIV strains such as SIVagm, SIVsun, SIVlhoest, and SIVrcm use Bonzo/ STRL33/CXCR6 in vitro but less BOB/GPR15.…”
Section: Cell Cycle Dysregulationmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV uses CXCR4 as an alternative coreceptor, whereas SIVs use several chemokine orphan receptors such as BOB/GPR15 and Bonzo/STRL33/CXCR6 for efficient infection and replication in vitro. [181][182][183] Several lines of evidence indicated that in vitro BOB/GPR15 is an important SIV coreceptor [184][185][186] exhibiting greater activity than CCR5. 184 Several reports have found that nonpathogenic SIV strains such as SIVagm, SIVsun, SIVlhoest, and SIVrcm use Bonzo/ STRL33/CXCR6 in vitro but less BOB/GPR15.…”
Section: Cell Cycle Dysregulationmentioning
confidence: 99%
“…[181][182][183] Several lines of evidence indicated that in vitro BOB/GPR15 is an important SIV coreceptor [184][185][186] exhibiting greater activity than CCR5. 184 Several reports have found that nonpathogenic SIV strains such as SIVagm, SIVsun, SIVlhoest, and SIVrcm use Bonzo/ STRL33/CXCR6 in vitro but less BOB/GPR15. [187][188][189] In contrast, pathogenic SIV strains (SIVmne, SIVmac) have been reported to use in vitro both CCR5 and BOB/GPR15 but not Bonzo/STLR33/CXCR6.…”
Section: Cell Cycle Dysregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to CXCR4 and CCR5, several other members of the 7TM receptor family, namely CCR1, CCR2B, CCR3, CCR4, CCR8, CCR9, GPR15\ BOB, STRL33\Bonzo, GPR1, V28 and Apj, can be used by some HIV and SIV isolates Berger, 1997 ;Choe et al, 1996Choe et al, , 1998Doranz et al, 1996 ;Rucker et al, 1997 ;Owen et al, 1998 ;Liao et al, 1997 ;Deng et al, 1997 ;Farzan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The tissue expression pattern of GPRl was also examined by others (Farran et al , 1997). GPRl mRNA transcripts were detected in U87 cells and human alveolar macrophages, but not in primary human T lymphocytes, activated rhesus macque PBMCs, or CEMx174 (Farzan et at., 1997).…”
Section: S N T Y R S E R T Y R a S P Leu A S P T Y R Tyr Ser Leu G L mentioning
confidence: 99%